2007
DOI: 10.5182/jaie.18.306
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Modified Hydroxyapatite

Abstract: Hydroxyapatite and its related calcium phosphate materials possess extremely high ability of ion exchange against various cations and anions. In this study, Si ion incorporated hydroxyapatites, •g modified hydroxyapatite•h, were synthesized by a chemical processing and subsequently hydrothermal-treatment in order to develop modified hydroxyapatites. The characterization of microstructure of these products was examined by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The syntheses of HAP substituted with other metals have been eagerly attempted by various synthetic processes, such as hydrothermal treatments, ion-exchange treatments, and normal heat-treatments at high temperature in order to enhance the ion exchange ability and bioactivity of HAP [9][10][11][12][13][14][15]. For example, Fe substituted HAP i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The syntheses of HAP substituted with other metals have been eagerly attempted by various synthetic processes, such as hydrothermal treatments, ion-exchange treatments, and normal heat-treatments at high temperature in order to enhance the ion exchange ability and bioactivity of HAP [9][10][11][12][13][14][15]. For example, Fe substituted HAP i.e.…”
Section: Introductionmentioning
confidence: 99%
“…13,14) Our previous study on HAp containing with SiO 2 sol indicated the possibility doping of SiO 2 to HAp by the hydrothermal process. [15][16][17][18][19][20] However, it has not come out about state of silicon in the silicon doped hydroxyapatite synthesized by hydrothermal technique. If SiO 2 segregated on surface of the sample, it might lead a danger to public health such as blood coagulation, infection.…”
Section: Introductionmentioning
confidence: 99%